Two-dimensional Ni(OH)2-XS2 (X = Mo and W) heterostructures. (25th September 2015) - Tang, Zhen-Kun; Tong, Chuan-Jia; Geng, Wei; Zhang, Deng-Yu; Liu, Li-Min
Abstract: Two-dimensional (2D) van der Waals (vdW) heterostructures have received a lot of attention because of their wide applications in electronics and optoelectronics. In this work, the electronic structures and optical properties of nickel hydroxides (Ni(OH)2 ) and transition metal dichalcogenides (XS2, X = Mo, W) heterostructures are studied by hybrid density functional theory. The results reveal that all the considered Ni(OH)2 -XS2 heterostructures are indirect semiconductors with a band gap of 0.040–0.825 eV. Additionally, the AB stacked Ni(OH)2 -XS2 heterostructures are more stable than the AA stacked one. Interestingly, the complete electron–hole separation is found in the Ni(OH)2 -XS2 heterostructure, and its conduction band minimum and valence band maximum are located on the XS2 and Ni(OH)2 layers, respectively. Besides, the optical absorption peaks of Ni(OH)2 -XS2 heterostructures are mainly located within the visible light region. These fascinating electronic structures and optical absorption of the Ni(OH)2 -XS2 heterostructures make them promising candidates for applications in 2D optoelectronics.